Composition, molding material, multilayer structure, molded body, food package, composition, and multilayer structure production method
By incorporating a specific trace amount of titanium compound and a lubricant at a specific mass ratio into an EVOH resin composition derived from biomass, the thermal stability issues of existing EVOH resin compositions are addressed, resulting in improved performance for packaging applications.
Patent Information
- Application Number
- JP2024166930
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-29
- Filing Date
- 2024-09-26
- Publication Date
- 2025-04-10
AI Technical Summary
Existing EVOH resin compositions derived from biomass have insufficient thermal stability, which limits their performance in packaging applications.
A composition containing an ethylene-vinyl alcohol copolymer derived from biomass, combined with a specific trace amount of titanium compound and a lubricant at a specific mass ratio, enhancing thermal stability.
The composition exhibits excellent thermal stability, improving the performance of molded materials, multilayer structures, and food packaging bodies.
Smart Images

Figure 2025060456000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a composition, a molding material, a multilayer structure, a molded article, a food packaging material, a composition, and a method for producing a multilayer structure. [Background technology]
[0002] Ethylene-vinyl alcohol copolymers (hereinafter sometimes referred to as "EVOH resins") are excellent in transparency, gas barrier properties such as oxygen and other gases, aroma retention, solvent resistance, oil resistance, mechanical strength, etc., and are formed into films, sheets, bottles, etc., and are widely used as various packaging materials such as food packaging materials, pharmaceutical packaging materials, industrial chemical packaging materials, and agricultural chemical packaging materials.
[0003] On the other hand, in recent years, there has been an increasing demand for bioplastics made from carbon-neutral biomass-derived raw materials, aiming for a recycling-oriented society. However, it is known that synthetic resins derived from biomass are sometimes inferior in performance to synthetic resins derived from fossil fuels. Therefore, research is being conducted on biomass-derived resins that are comparable in performance to fossil fuel-derived resins by combining raw materials derived from biomass and raw materials derived from fossil fuels.
[0004] For example, Patent Documents 1 and 2 disclose a gas barrier resin composition in which part of the ethylene and vinyl ester raw materials of the EVOH resin are derived from biomass, and disclose that the composition has gas barrier properties and long-run properties comparable to those of a composition using only raw materials derived from fossil fuels. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2022-13857 A [Patent Document 2] Patent Publication No. 2022-27726 Summary of the Invention [Problem to be solved by the invention]
[0006] According to the inventors' investigations, the techniques disclosed in the above Patent Documents 1 and 2 have insufficient thermal stability, and there is room for further improvement in thermal stability.
[0007] In view of the above, an object of the present invention is to provide a resin composition having excellent thermal stability, even if it is an EVOH resin using a raw material derived from biomass. [Means for solving the problem]
[0008] However, in light of these circumstances, the inventors conducted extensive research and discovered that an EVOH resin, part of which is made from raw materials derived from biomass, can have excellent thermal stability by containing a specific trace amount of a titanium compound and the lubricant and titanium compound in a specific mass ratio, thereby completing the present invention.
[0009] That is, the present invention has the following aspects. [1] A composition comprising an ethylene-vinyl alcohol copolymer, a titanium compound, and a lubricant, At least a portion of the ethylene-vinyl alcohol copolymer is derived from biomass; The content of the titanium compound in terms of metal is 0.0001 ppm or more and less than 1 ppm based on the mass of the composition, A composition, wherein a mass ratio of the content of the lubricant to the content of the titanium compound calculated as metal is 500 to 280,000. [2] The composition according to [1], wherein the content of the titanium compound in terms of metal is 0.0001 ppm or more and 0.8 ppm or less based on the mass of the composition. [3] The composition according to [1] or [2], wherein the ethylene-vinyl alcohol copolymer has a bio-based content of 0.01 to 99%. [4] The composition according to any one of [1] to [3], wherein the ethylene-vinyl alcohol copolymer has a bio-based content of 1 to 99%. [5] A molding material comprising the composition according to any one of [1] to [4]. [6] A multilayer structure having a layer containing the composition according to any one of [1] to [4]. [7] The multilayer structure according to [6], further comprising an adhesive resin layer. [8] A molded article comprising the multilayer structure according to [6] or [7]. [9] A food packaging body comprising the multilayer structure according to [6] or [7].
[10] A method for producing the composition according to any one of [1] to [4], A method for producing a composition, comprising the step of mixing the ethylene-vinyl alcohol copolymer and the titanium compound.
[11] A method for producing a multilayer structure according to [6] or [7], comprising the steps of: A method for producing a multilayer structure, comprising the step of melt-molding a layer comprising the composition. Effect of the Invention
[0010] The composition of the present invention has excellent heat stability. In addition, a molding material formed from the composition of the present invention, and a multilayer structure, a molded article, and a food package having a layer containing the composition of the present invention also have excellent heat stability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention will be described below based on examples of the mode for carrying out the present invention. However, the present invention is not limited to the embodiment described below.
[0012] In this specification, "x and / or y (x and y are optional configurations)" means at least one of x and y, and means three possibilities: x only, y only, and x and y. When expressed as "X to Y" (X and Y are arbitrary numbers), unless otherwise specified, it includes the meaning of "X or more and Y or less", as well as "preferably more than X" or "preferably less than Y". When expressed as "X or more" (X is any number) or "Y or less" (Y is any number), this also includes the meaning of "preferably more than X" or "preferably less than Y." In the present specification, the upper or lower limit of a numerical range described in stages can be arbitrarily combined with the upper or lower limit of a numerical range of another stage. In addition, in the numerical range described in this specification, the upper or lower limit of the numerical range can be replaced with a value shown in the examples. In this specification, the term "layer" includes not only a thick layer but also a relatively thin layer such as a "film," a "tape," or a "sheet."
[0013] <Composition> A composition according to one embodiment of the present invention (hereinafter, sometimes referred to as "the composition") contains an EVOH resin as an essential component, a specific trace amount of a titanium compound, and the lubricant and the titanium compound in a specific mass ratio. That is, the content of the EVOH resin in the composition is usually 1% by mass or more, preferably 10% by mass or more, more preferably 50% by mass or more, even more preferably 60% by mass or more, particularly preferably 70% by mass or more, especially preferably 80% by mass or more, especially more preferably 90% by mass or more, and still more preferably 95% by mass or more. The upper limit is 100% by mass, and may be 99% by mass, for example, 1 to 100% by mass, or 10 to 99% by mass. Each component will be described below.
[0014] [EVOH resin] The EVOH resin used in the present embodiment is at least partially derived from biomass. More specifically, it refers to an EVOH resin in which at least a part of the ethylene structural units, vinyl alcohol structural units, and vinyl ester structural units of the EVOH resin are derived from biomass.
[0015] The EVOH resin is a water-insoluble thermoplastic resin obtained by saponifying an ethylene-vinyl ester copolymer, which is a copolymer of ethylene and vinyl ester, at least a portion of which is derived from biomass.
[0016] The biobased content of ethylene and / or vinyl ester used as raw materials can be confirmed to be derived from biomass by measuring the biobased content. The biobased content is an index that indicates the proportion of raw materials derived from biomass. In this specification, it is measured by measuring the radioactive carbon [ 14 The bio-based carbon content is determined by measuring the concentration of carbon-14 (hereinafter referred to as "carbon-14"). Specifically, the bio-based content can be measured according to the method described in ASTM D6866-18. That is, when the bio-based content of an EVOH resin is more than 0% and 100% or less, it can usually be said that the ethylene and / or vinyl ester used as the raw material contains biomass-derived material.
[0017] "Biomass" refers to organic resources derived from plants and animals, excluding those derived from fossil fuels (fossil resources). From the standpoint of cost and the environment, it is preferable for biomass to be an organic resource derived from plants, that is, derived from biological raw materials.
[0018] Biomass-derived ethylene can be produced, for example, by refining bioethanol from a biomass raw material and carrying out a dehydration reaction. For example, vinyl esters derived from biomass can be produced by a general industrial process in which ethylene, acetic acid, and molecular oxygen are reacted using a palladium catalyst.
[0019] Examples of biomass raw materials include waste materials, unused materials, and resource crop materials, such as cellulose crops (pulp, kenaf, wheat straw, rice straw, waste paper, papermaking residues, etc.), wood, charcoal, compost, natural rubber, cotton, sugarcane, soybean pulp, oils and fats (rapeseed oil, cottonseed oil, soybean oil, coconut oil, castor oil, etc.), carbohydrate crops (corn, potatoes, wheat, rice, rice husks, rice bran, old rice, cassava, sago palm, etc.), bagasse, buckwheat, soybeans, essential oils (pine oil, orange oil, eucalyptus oil, etc.), pulp black liquor, vegetable oil residue, etc. These can be used alone or in combination of two or more.
[0020] Examples of methods for producing bioethanol include a method in which biomass raw materials are pretreated as necessary (compressed hot water treatment, acid treatment, alkali treatment, saccharification treatment using saccharifying enzymes), then fermented with yeast to produce bioethanol, and then the bioethanol is purified through a distillation process and a dehydration process. When saccharification treatment is performed during bioethanol production, sequential saccharification and fermentation in which saccharification and fermentation are performed in stages may be used, or parallel saccharification and fermentation in which saccharification and fermentation are performed simultaneously may be used, but from the viewpoint of production efficiency, it is preferable to produce bioethanol by parallel saccharification and fermentation.
[0021] The ratio of the ethylene structural units derived from biomass in the total ethylene structural units constituting the EVOH resin may be derived from biomass, but is usually 0.001 to 100 mol%, preferably 5 to 98 mol%, more preferably 15 to 97 mol%, even more preferably 25 to 96 mol%, and particularly preferably 35 to 95 mol%. The ratio of the ethylene structural units derived from fossil fuel in the total ethylene structural units constituting the EVOH resin is usually 99.999 mol% or less, preferably 95 mol% or less, more preferably 85 mol% or less, even more preferably 75 mol% or less, and particularly preferably 65 mol% or less. The lower limit is 0 mol%, for example, 0 to 99.999 mol%. The total ethylene structural units may not contain ethylene structural units derived from fossil fuel. When the ratio of the ethylene structural units derived from biomass in the total ethylene structural units constituting the EVOH resin is high, the bio-based degree of the present composition is high, and the environmental load tends to be reduced. In addition, when the EVOH resin contains biomass-derived vinyl ester structural units and / or vinyl alcohol structural units, the ratio of biomass-derived ethylene structural units to all ethylene structural units may be 0.
[0022] As a vinyl ester other than the vinyl ester derived from biomass, vinyl acetate is typically used because of its good market availability and efficiency in treating impurities during production. Examples of vinyl esters other than vinyl acetate include aliphatic vinyl esters such as vinyl formate, vinyl propionate, vinyl valerate, vinyl butyrate, vinyl isobutyrate, vinyl pivalate, vinyl caprate, vinyl laurate, vinyl stearate, and vinyl versatate, and aromatic vinyl esters such as vinyl benzoate, and the like. In general, aliphatic vinyl esters having 3 to 20 carbon atoms, preferably 4 to 10 carbon atoms, and more preferably 4 to 7 carbon atoms are used. These are usually used alone, but multiple types may be used simultaneously as necessary.
[0023] Examples of biomass-derived vinyl esters include vinyl esters produced using ethylene derived from biomass, specifically vinyl acetate in which the carbon of the vinyl group portion is derived from biomass.
[0024] A method for producing a vinyl ester derived from biomass includes, for example, a general industrial method of reacting ethylene, acetic acid, and oxygen molecules using a palladium catalyst. The vinyl ester derived from biomass may be a vinyl ester produced using a carboxylic acid derived from biomass. When the saponification degree of the EVOH resin is not 100 mol%, acyl groups derived from biomass remain.
[0025] The ratio of the vinyl alcohol structural unit derived from biomass in all the vinyl alcohol structural units (vinyl ester structural units) constituting the EVOH resin is usually 0.001 to 100 mol%, preferably 5 to 98 mol%, more preferably 15 to 97 mol%, further preferably 25 to 96 mol%, particularly preferably 35 to 95 mol%. The ratio of the vinyl alcohol structural unit derived from fossil fuel in all the vinyl alcohol structural units constituting the EVOH resin is usually 99.999 mol% or less, preferably 95 mol% or less, more preferably 85 mol% or less, further preferably 75 mol% or less, particularly preferably 65 mol% or less. The lower limit is 0 mol%, for example, 0 to 99.999 mol%. The vinyl alcohol structural unit derived from fossil fuel may not be included in all the vinyl alcohol structural units. When the ratio of the vinyl alcohol structural unit derived from biomass in all the vinyl alcohol structural units constituting the EVOH resin is high, the bio-based degree of the present composition is increased, and the environmental load tends to be reduced.
[0026] In addition, when the EVOH resin contains biomass-derived ethylene structural units, the ratio of the total of the biomass-derived vinyl ester structural units and the biomass-derived vinyl alcohol structural units to the total of the vinyl ester structural units and the vinyl alcohol structural units may be 0.
[0027] The fact that the EVOH resin is derived from biomass can be confirmed by confirming the presence of "sulfur compounds" and / or "carbon-14" in the composition. "Sulfur compounds" and / or "carbon 14" are impurities derived from biomass, and their presence cannot be confirmed in petroleum-derived EVOH resin, but their presence can be confirmed in biomass-derived EVOH resin.
[0028] It is said that EVOH resin has problems with thermal stability, and it is speculated that the main cause of thermal decomposition in particular is the polyene structure formed in the main chain of EVOH resin due to a dehydration reaction starting from the hydroxyl group. It is speculated that by using EVOH resin derived from biomass in this composition, the primary isotope effect of carbon-14 (increased bond energy) will slow down the thermal decomposition rate of the EVOH resin itself, improving thermal stability.
[0029] The EVOH resin has an ethylene structural unit content of usually 20 to 60 mol%, preferably 25 to 50 mol%, and particularly preferably 25 to 35 mol%. When the content is equal to or more than the lower limit, the gas barrier property under high humidity and melt moldability tend to be excellent, whereas when the content is equal to or less than the upper limit, the gas barrier property tends to be excellent. In the present embodiment, the ethylene structural unit content of the EVOH resin refers to a value measured based on ISO14663.
[0030] The saponification degree of the EVOH resin is usually 90 to 100 mol%, preferably 95 to 100 mol%, and more preferably 99 to 100 mol%. When the saponification degree is equal to or higher than the lower limit, the EVOH resin tends to have excellent gas barrier properties, thermal stability, moisture resistance, etc. The degree of saponification of the EVOH resin can be measured based on JIS K6726 (however, the EVOH resin is used as a solution uniformly dissolved in a water / methanol solvent).
[0031] The melt flow rate (MFR) of the EVOH resin (210°C, load 2160 g) is usually 0.5 to 100 g / 10 min, preferably 1 to 50 g / 10 min, and more preferably 3 to 35 g / 10 min. When the MFR is equal to or lower than the upper limit, the stability during film formation tends to be excellent, and when the MFR is equal to or higher than the lower limit, the viscosity becomes appropriate and the melt extrusion tends to be excellent. The MFR is an index of the degree of polymerization of the EVOH resin, and can be adjusted by the amount of the polymerization initiator and the amount of the solvent used when copolymerizing ethylene and the vinyl ester.
[0032] The bio-based content of the EVOH resin is usually 0.001 to 100%, preferably 1 to 99%, more preferably 20 to 86%, further preferably 38 to 76%, and particularly preferably 58 to 66%. The upper limit is 100%.
[0033] In addition, the EVOH resin may further contain structural units derived from the comonomers shown below (for example, 10 mol % or less of the EVOH resin) to the extent that the effects of this embodiment are not impaired. Examples of the comonomer include olefins such as propylene, 1-butene, and isobutene; hydroxyl-containing α-olefins such as 3-butene-1-ol, 3-butene-1,2-diol, 4-pentene-1-ol, and 5-hexene-1,2-diol, and derivatives thereof such as esters and acylation products; hydroxyalkylvinylidenes such as 2-methylenepropane-1,3-diol and 3-methylenepentane-1,5-diol; 1,3-diacetoxy-2-methylenepropane, 1,3-dipropionyloxy-2-methylenepropane, and 1,3-dibutyloxy. hydroxyalkylvinylidene diacetates such as aryloxy-2-methylenepropane; unsaturated acids such as acrylic acid, methacrylic acid, crotonic acid, (anhydrous) phthalic acid, (anhydrous) maleic acid, (anhydrous) itaconic acid, or their salts or mono- or dialkyl esters having an alkyl group with 1 to 18 carbon atoms; acrylamide, N-alkylacrylamide having an alkyl group with 1 to 18 carbon atoms, N,N-dimethylacrylamide, 2-acrylamidopropanesulfonic acid or its salts, acrylamidopropyldimethylamine or its acid salts or its quaternary salts. acrylamides such as methacrylamide, N-alkyl methacrylamides having an alkyl group with 1 to 18 carbon atoms, N,N-dimethyl methacrylamide, 2-methacrylamidopropanesulfonic acid or its salts, methacrylamidepropyldimethylamine or its acid salts or its quaternary salts; N-vinyl amides such as N-vinylpyrrolidone, N-vinylformamide, and N-vinylacetamide; vinyl cyanides such as acrylonitrile and methacrylonitrile; alkyl vinyl ethers having an alkyl group with 1 to 18 carbon atoms, hydrochloride, etc. vinyl ethers such as alkoxyalkyl vinyl ether and alkoxyalkyl vinyl ether; halogenated vinyl compounds such as vinyl chloride, vinylidene chloride, vinyl fluoride, vinylidene fluoride and vinyl bromide; vinyl silanes such as trimethoxyvinylsilane; halogenated allyl compounds such as allyl acetate and allyl chloride; allyl alcohols such as allyl alcohol and dimethoxyallyl alcohol; and comonomers such as trimethyl-(3-acrylamido-3-dimethylpropyl)-ammonium chloride and acrylamido-2-methylpropanesulfonic acid.These can be used alone or in combination of two or more.
[0034] Among them, hydroxyl group-containing α-olefins are preferred, and 3-butene-1,2-diol and 5-hexene-1,2-diol are particularly preferred. When the hydroxyl group-containing α-olefins are copolymerized, the resulting EVOH resin has a primary hydroxyl group in the side chain. Such an EVOH resin having a primary hydroxyl group in the side chain, particularly an EVOH resin having a 1,2-diol structure in the side chain, is preferred in that it has good secondary moldability while maintaining gas barrier properties.
[0035] When the EVOH resin has a primary hydroxyl group in a side chain, the content of the structural unit derived from the monomer having the primary hydroxyl group is usually 0.1 to 20 mol %, preferably 0.5 to 15 mol %, and particularly preferably 1 to 10 mol % of the EVOH resin.
[0036] As the EVOH resin, there can also be used EVOH resins that have been "post-modified" by esterification, urethanization, acetalization, cyanoethylation, oxyalkylenation, or the like.
[0037] When the post-modified EVOH resin is used, the modification rate is usually 10 mol% or less, and preferably 4 mol% or less. The lower limit is usually 0.01 mol% or more, and preferably 0.1 mol% or more, for example, 0.01 to 10 mol%, and preferably 0.1 to 4 mol%. When the modification rate of the EVOH resin is within the above range, the resin tends to have excellent heat deterioration prevention properties and long-run properties.
[0038] Furthermore, the EVOH resin may be a mixture of EVOH resins having different contents of ethylene structural units, degrees of saponification, degrees of polymerization, copolymerization components, and the like.
[0039] As described above, the EVOH resin used in the present embodiment is obtained by saponifying a copolymer of ethylene and vinyl ester, at least a part of which is derived from biomass. The copolymerization can be carried out by any known polymerization method, such as solution polymerization, suspension polymerization, emulsion polymerization, etc.
[0040] The polymerization solvent may be, for example, a lower alcohol such as methanol, ethanol, propanol, or butanol, or a ketone such as acetone or methyl ethyl ketone, and may be used alone or in combination of two or more. Methanol is preferably used as the polymerization solvent in industrial applications.
[0041] The amount of the polymerization solvent used may be appropriately selected in accordance with the polymerization degree of the target copolymer, taking into consideration the chain transfer constant of the polymerization solvent. For example, when the polymerization solvent is methanol, the amount is selected from the range of S (polymerization solvent) / M (monomer)=0.01 to 10 (mass ratio), preferably about 0.05 to 7 (mass ratio).
[0042] Examples of the polymerization catalyst include known radical polymerization catalysts such as azobisisobutyronitrile, acetyl peroxide, benzoyl peroxide, and lauryl peroxide, and low-temperature active radical polymerization catalysts. Examples of the low-temperature active radical polymerization catalyst include peroxyesters such as t-butyl peroxyneodecanoate, t-butyl peroxypivalate, α,α'-bis(neodecanoylperoxy)diisopropylbenzene, cumyl peroxyneodecanoate, 1,1,3,3,-tetramethylbutyl peroxyneodecanoate, 1-cyclohexyl-1-methylethyl peroxyneodecanoate, t-hexyl peroxyneodecanoate, and t-hexyl peroxypivalate, di-n-propyl peroxydicarbonate, di-iso-propyl peroxydicarbonate, di-sec-butyl peroxydicarbonate, bis(4- Examples of the peroxydicarbonates include peroxydicarbonates such as t-butylcyclohexyl)peroxydicarbonate, di-2-ethoxyethyl peroxydicarbonate, di(2-ethylhexyl)peroxydicarbonate, dimethoxybutyl peroxydicarbonate, and di(3-methyl-3-methoxybutylperoxy)dicarbonate; organic peroxides such as diacyl peroxides such as 3,3,5-trimethylhexanoyl peroxide, diisobutyryl peroxide, and lauroyl peroxide; and azo compounds such as 2,2'-azobis-(2,4-dimethylvaleronitrile) and 2,2'-azobis-(4-methoxy-2,4-dimethylvaleronitrile). The low-temperature active radical polymerization catalyst refers to an organic compound having a half-life of 10 to 300 minutes at 60°C. These polymerization catalysts may be used alone or in combination of two or more.
[0043] The amount of the polymerization catalyst used varies depending on the type of catalyst and cannot be generally determined, but is selected arbitrarily depending on the polymerization rate. For example, when azobisisobutyronitrile or acetyl peroxide is used, the amount is preferably 0.001 to 0.2 parts by mass, more preferably 0.005 to 0.1 parts by mass, per 100 parts by mass of the vinyl ester monomer.
[0044] The method for introducing ethylene into the copolymer may be a normal pressurized polymerization of ethylene. The amount of ethylene introduced can be controlled by the pressure of ethylene, which is usually selected from the range of 2.0 to 8.0 MPa, although it depends on the desired ethylene structural unit content and cannot be generally determined.
[0045] The reaction temperature of the copolymerization reaction depends on the polymerization solvent and pressure used, and cannot be generally determined, but is usually below the boiling point of the polymerization solvent, and is usually preferably 40 to 80° C., particularly preferably 55 to 80° C. If the temperature is equal to or higher than the lower limit, the polymerization proceeds appropriately, and therefore there is no need to set a large amount of catalyst to shorten the polymerization time, and conversely, if the temperature is equal to or lower than the upper limit, polymerization control tends to be excellent.
[0046] In addition, the polymerization time is usually 4 to 10 hours, and more preferably 6 to 9 hours, in the case of a batch process. If the polymerization time is equal to or more than the lower limit, there is a tendency that it is not necessary to increase the polymerization temperature or set a large amount of catalyst, and conversely, if it is equal to or less than the upper limit, there is a tendency that productivity is excellent. In the case of a continuous process, the average residence time in the polymerization tank is usually 2 to 8 hours, and more preferably 2 to 6 hours. If the residence time is equal to or more than the lower limit, there is a tendency that it is not necessary to increase the polymerization temperature or set a large amount of catalyst, and conversely, if the polymerization time is equal to or less than the upper limit, there is a tendency that productivity is excellent.
[0047] The polymerization rate is set as high as possible within the range where polymerization control is possible from the viewpoint of productivity, and is preferably 30 to 60%. When the polymerization rate is equal to or higher than the lower limit, the productivity is excellent and there is a tendency to prevent a large amount of unpolymerized vinyl ester monomer from remaining, whereas when the polymerization rate is equal to or lower than the upper limit, there is a tendency to excellent polymerization control.
[0048] The ethylene-vinyl ester copolymer thus obtained is saponified to obtain the EVOH resin of the present embodiment. The saponification is carried out using a saponification catalyst in a state where the ethylene-vinyl ester copolymer obtained above is dissolved in alcohol or water-containing alcohol.
[0049] Examples of the alcohol include lower alcohols having 1 to 5 carbon atoms, such as methanol, ethanol, and propanol. These may be used alone or in combination of two or more. Among these, methanol is preferred.
[0050] The concentration of the ethylene-vinyl ester copolymer in the alcohol is appropriately selected depending on the viscosity, and is usually 5 to 60% by mass.
[0051] Examples of the saponification catalyst include alkali catalysts such as hydroxides or alcoholates of alkali metals, such as sodium hydroxide, potassium hydroxide, sodium methylate, sodium ethylate, potassium methylate, and potassium ethylate, and acid catalysts such as sulfuric acid, hydrochloric acid, nitric acid, metasulfonic acid, zeolite, and cation exchange resins. These may be used alone or in combination of two or more kinds. Among these, alkali catalysts such as hydroxides and alcoholates of alkali metals are preferred.
[0052] The temperature at which the saponification is carried out is not limited, but is preferably 20 to 140° C., and the saponification time is preferably 1 to 5 hours.
[0053] The EVOH resin thus produced may be at least partially derived from biomass, and preferably the ethylene structural unit and / or the vinyl alcohol structural unit are derived from biomass, and more preferably, from the viewpoint of availability, the vinyl alcohol structural unit is derived from biomass. Such an EVOH resin mainly comprises ethylene structural units and vinyl alcohol structural units, and if necessary, contains a small amount of vinyl ester structural units remaining without being saponified. When another comonomer is copolymerized, the resin further contains structural units derived from the comonomer.
[0054] In this specification, the term "mainly" refers to the component that constitutes the majority in the target object, and typically, it is preferably 50 mass% or more of the target object, more preferably 60 mass% or more, even more preferably 70 mass% or more, particularly preferably 80 mass% or more, and especially preferably 90 mass% or more, and may even be 100 mass%.
[0055] Moreover, the EVOH resin produced by the above-mentioned production method is contained in an alcohol-based solvent, and the content of the EVOH resin in the EVOH resin solution is preferably about 10 to 50 mass % from the viewpoint of producing the EVOH resin pellets described below.
[0056] The EVOH resin used in the present composition may be the alcohol solvent of the EVOH resin produced by the above-mentioned production method, but is preferably in the form of pellets. The shape and size of the pellets are preferably the same as those of the composition described below.
[0057] The pellets thus produced are preferably washed by immersing them in an aqueous solution of an acid and / or its salt, and examples of such an acid include formic acid, acetic acid, adipic acid, phosphoric acid, boric acid, or its salt, and preferably acetic acid. After that, the pellets are preferably washed with water.
[0058] The chemically treated and washed pellets may then be dried appropriately, and the preferred drying method is to use a fluidized hot air dryer or a stationary hot air dryer. In this manner, pellets of the EVOH resin can be produced.
[0059] [Titanium compounds] The titanium compound may be, for example, an inorganic titanium compound or an organic titanium compound. The titanium compounds may be used alone or in combination of two or more kinds. Among them, inorganic titanium compounds are preferred.
[0060] Examples of the inorganic titanium compound include titanium oxide, titanium hydroxide, titanium chloride, and inorganic salts of titanium.
[0061] Examples of the titanium oxide include titanium oxide (II), titanium oxide (III), titanium oxide (IV), and titanium zincide. Examples of the titanium hydroxide include titanium(I) hydroxide and titanium(II) hydroxide. Examples of the titanium chloride include titanium(I) chloride and titanium(II) chloride. Examples of the titanium inorganic salt include titanium phosphate and titanium sulfate. Among these, titanium oxide is preferred, titanium(IV) oxide is more preferred, and rutile-type titanium(IV) oxide is particularly preferred.
[0062] Examples of the organic titanium compound include titanium carboxylates such as titanium acetate, titanium butyrate, and titanium stearate.
[0063] The titanium compound may exist in the composition as a titanium compound, or may exist in an ionized state or in a complex state interacting with the EVOH resin or other ligands.
[0064] The average particle size of the titanium compound is usually 0.001 to 100 μm, preferably 0.01 to 50 μm, and more preferably 0.015 to 20 μm. When the average particle size of the titanium compound is within the above range, the coloring suppression effect tends to be more excellent. The average particle size can be measured by a predetermined method, such as dynamic light scattering (DLS) or sedimentation velocity method.
[0065] The content of the titanium compound in terms of metal is 0.0001 ppm or more and less than 1 ppm, preferably 0.0001 to 0.8 ppm, more preferably 0.0005 to 0.5 ppm, even more preferably 0.001 to 0.3 ppm, particularly preferably 0.005 to 0.2 ppm, and particularly preferably 0.01 to 0.1 ppm, based on the mass of the composition. When the content of the titanium compound is equal to or less than the upper limit, the thermal decomposition of the EVOH resin is prevented and the coloring prevention property tends to be excellent, and when the content is equal to or more than the lower limit, the thermal deterioration tends to be suppressed. The content of the titanium compound in terms of metal is, in other words, the content of titanium element.
[0066] The content of the titanium compound in terms of metal can be quantified by weighing the composition into a platinum crucible, incinerating it using a burner and an electric furnace, decomposing the incinerated product by heating it with nitric acid and hydrofluoric acid, treating it with a mixed acid of dilute nitric acid and dilute hydrofluoric acid, and measuring the titanium in the constant volume solution obtained by constant volume measurement using an ICP mass spectrometer (Agilent 8800, manufactured by Agilent Technologies) by ICP mass spectrometry.
[0067] [Lubricant] The lubricant may, for example, be a higher fatty acid having 12 to 25 carbon atoms, preferably a higher fatty acid having 13 to 23 carbon atoms, and more preferably a higher fatty acid having 15 to 20 carbon atoms. Examples of the higher fatty acids include higher fatty acids such as lauric acid, myristic acid, palmitic acid, stearic acid, behenic acid, and oleic acid, and metal salts of higher fatty acids such as aluminum salts, calcium salts, zinc salts, magnesium salts, and barium salts of these higher fatty acids; esters of higher fatty acids such as methyl esters, isopropyl esters, butyl esters, and octyl esters of the higher fatty acids; saturated higher fatty acid amides such as stearic acid amide and behenic acid amide, unsaturated higher fatty acid amides such as oleic acid amide and erucic acid amide; and amides of higher fatty acids such as bis-higher fatty acid amides such as ethylene bisstearic acid amide, ethylene bisoleic acid amide, ethylene biserucic acid amide, and ethylene bislauric acid amide. Examples of lubricants other than the higher fatty acids include low molecular weight polyethylene having a molecular weight of about 500 to 10,000 (preferably less than 10,000, more preferably 9,000 or less), low molecular weight polypropylene, or low molecular weight polyolefins such as acid-modified products thereof, higher alcohols, ester oligomers, and fluoroethylene resins. These lubricants can be used alone or in combination of two or more kinds.
[0068] From the viewpoints of extrusion stability and market availability, the valence of the higher fatty acids is usually 1 to 5, preferably 1 to 3, and more preferably 1 to 2. The valence means the number of structures derived from higher fatty acids in one molecule of the compound used in the lubricant, and for example, when bisstearic acid amide is used as the lubricant, it has two structures derived from higher fatty acid molecules having 18 carbon atoms in one molecule, so it is an amide of a higher fatty acid having 18 carbon atoms, and the valence of the higher fatty acid is 2.
[0069] Among the above-mentioned lubricants, preferred are higher fatty acids, metal salts of higher fatty acids, esters of higher fatty acids, and amides of higher fatty acids, more preferred are metal salts of higher fatty acids and amides of higher fatty acids, and from the viewpoint of extrusion stability, still more preferred are amides of higher fatty acids, and particularly preferred is ethylene bisstearamide.
[0070] The lubricant may be in any form, such as a solid (powder, fine powder, flakes, etc.), semisolid, liquid, paste, solution, emulsion (aqueous dispersion), etc. Among these, a powder form is preferred. The particle size of the powder lubricant is usually 0.1 to 100 μm, preferably 1 to 75 μm, and more preferably 5 to 50 μm.
[0071] The content of the lubricant is preferably 10000 ppm or less, more preferably 9500 ppm or less, even more preferably 9000 ppm or less, particularly preferably 8500 ppm or less, and most preferably 100 ppm or less, based on the mass of the composition. When the content of the lubricant is equal to or less than the upper limit, the composition tends to have excellent thermal stability. The lower limit of the content of the lubricant is usually 1 ppm, preferably 10 ppm or more, more preferably 30 ppm or more, and even more preferably 50 ppm or more, and the range is, for example, usually 1 to 10000 ppm. When the content of the lubricant is equal to or more than the lower limit, the composition tends to have excellent moldability.
[0072] The content of the lubricant can be measured, for example, by the following method. When the lubricant is applied to the surface of the EVOH resin, the amount of the lubricant added can be considered as the content. Furthermore, when a lubricant is contained in the composition, if the lubricant is, for example, a higher fatty acid amide, the total amount of nitrogen in the composition can be measured using a total nitrogen trace analyzer and converted into the lubricant content, thereby measuring the lubricant content in the composition.
[0073] The mass ratio of the content of the lubricant to the content of the titanium compound in terms of metal [lubricant content / metal content of titanium compound] is usually 500 to 280000, preferably 600 to 250000, more preferably 800 to 230000, and particularly preferably 1000 to 200000. When this value is equal to or less than the upper limit, coloration tends to be easily suppressed, and when it is equal to or more than the lower limit, an effect of suppressing thermal degradation tends to be obtained.
[0074] It is generally known that EVOH resins become discolored due to thermal degradation. This is because EVOH resins deteriorate due to heat, generating radicals, which cause dehydration reactions in the hydroxyl groups of the EVOH resin, resulting in the formation of double bond structures in the main chain of the EVOH resin. These sites then become reaction initiation sites, which further cause dehydration reactions, etc., resulting in the formation of polyene structures in the main chain of the EVOH resin.
[0075] In contrast, the composition of the present invention contains a specific trace amount of a titanium compound, which suppresses color change due to thermal degradation of the EVOH resin and provides excellent long-run properties. Generally, when a titanium compound is contained in a composition, it is believed that the composition will be colored by titanium ions, and therefore it is common technical knowledge for a person skilled in the art to avoid the use of titanium compounds.
[0076] However, in the present embodiment, contrary to such common technical knowledge, it has been discovered that when a specific trace amount of a titanium compound and a lubricant are contained and the two are used in a specific mass ratio, a composition in which color change due to thermal degradation is suppressed can be obtained.
[0077] Titanium is stable as a tetravalent ion and stabilizes the EVOH resin by coordinating with the double bonds in the main chain and forming a chelate, etc., and it is presumed that this suppresses the formation of polyene structures in the main chain of the EVOH resin. It is also believed that the coexistence of the lubricant with the titanium compound suppresses any reaction that may occur between the lubricant and the composition, thereby suppressing the tendency to thicken and improving the thermal stability. On the other hand, when the content of the titanium compound is within a specific range, it is thought that there is a tendency that deterioration due to thermal decomposition of the EVOH resin caused by the titanium compound can be suppressed.
[0078] [Other thermoplastic resins] The present composition may contain a thermoplastic resin other than the EVOH resin within a range that does not impair the effects of the present invention (for example, usually 50% by mass or less of the present composition, preferably 30% by mass or less, more preferably 20% by mass or less, particularly preferably 10% by mass or less. The lower limit is 0% by mass, for example, 0 to 50% by mass). As the other thermoplastic resin, a known thermoplastic resin may be used, for example, a polyester resin, a polystyrene resin, a polyvinyl chloride resin, a polycarbonate resin, an ionomer, polyvinylidene chloride, a polyester elastomer, a polyurethane elastomer, a chlorinated polyethylene, a chlorinated polypropylene, etc. These may be used alone or in combination of two or more kinds.
[0079] [Other compounding agents] The composition may contain additives (however, the additives referred to here are used to mean excluding titanium compounds and lubricants) that are generally blended with EVOH resins, within a range that does not impair the effects of the present invention (for example, 5% by mass or less, preferably 3% by mass or less, the lower limit being 0% by mass, for example, 0 to 5% by mass). Examples of the additives include inorganic double salts (for example, hydrotalcite, etc.), plasticizers (for example, aliphatic polyhydric alcohols such as ethylene glycol, glycerin, hexanediol, etc., excluding those used as lubricants), oxygen absorbers [for example, inorganic oxygen absorbers such as aluminum powder and potassium sulfite; ascorbic acid, and further its fatty acid esters and metal salts, etc. (excluding those used as lubricants), gallic acid, polyhydric phenols such as hydroxyl group-containing phenol aldehyde resins, terpene compounds, blends of tertiary hydrogen-containing resins and transition metals (for example, a combination of polypropylene and cobalt), carbon-carbon Blends of unsaturated bond-containing resins and transition metals (e.g., a combination of polybutadiene and cobalt), photooxidative decomposition resins (e.g., polyketones), anthraquinone polymers (e.g., polyvinyl anthraquinone), and the like, and further polymer-based oxygen absorbers such as those obtained by adding photoinitiators (benzophenone, etc.) and antioxidants and deodorants other than those mentioned above (activated carbon, etc.), heat stabilizers (boric acid, phosphoric acid), light stabilizers, ultraviolet absorbers, colorants, antistatic agents, surfactants (excluding those used as lubricants), antibacterial agents, antiblocking agents, fillers (e.g., aluminum, inorganic fillers, etc.), etc. may be blended. These compounds may be used alone or in combination of two or more.
[0080] [Method of producing the composition] The composition can be produced, for example, by mixing the EVOH resin, titanium compound, and lubricant by a known method, such as a dry blend method, a melt mixing method, a solution mixing method, an impregnation method, etc., and among these, it is preferable to produce the composition by a method including a step of mixing the EVOH resin and the titanium compound. Also, these production methods can be arbitrarily combined.
[0081] The dry blending method may, for example, be (i) a method in which a pellet-shaped EVOH resin is dry-blended with a titanium compound and / or a lubricant using a tumbler or the like.
[0082] Examples of the melt mixing method include (ii) a method in which a pellet-shaped EVOH resin is dry-blended with a titanium compound and / or a lubricant, and the resulting dry blend is melt-kneaded, and (iii) a method in which a titanium compound and / or a lubricant is added to a molten EVOH resin, and the resulting mixture is melt-kneaded.
[0083] Examples of the solution mixing method include (iv) a method in which a solution is prepared using a commercially available EVOH resin, a titanium compound and / or a lubricant is added thereto, the solution is solidified and molded, and then the solution is subjected to solid-liquid separation by known means and dried; and (v) a method in which a titanium compound and / or a lubricant is added to an ethylene-vinyl ester copolymer solution before saponification or a homogeneous solution of an EVOH resin (such as a water / alcohol solution) during the production process of an EVOH resin, the solution is solidified and molded, and then the solution is subjected to solid-liquid separation by known means and dried.
[0084] The impregnation method includes, for example, (vi) a method in which pelletized EVOH resin is contacted with an aqueous solution containing a titanium compound and / or a lubricant to incorporate the titanium compound and / or the lubricant into the EVOH resin, and then the EVOH resin is dried. The aqueous solution containing a titanium compound may be an aqueous solution of a titanium compound or a titanium compound immersed in water containing various chemicals to elute titanium ions.
[0085] In the impregnation method, the content of the titanium compound (converted to metal) can be controlled by the concentration of the titanium compound in the aqueous solution in which the EVOH resin is immersed, the immersion temperature, the immersion time, and the like. The immersion temperature and immersion time are usually 0.5 to 48 hours, preferably 1 to 36 hours, and the immersion temperature is usually 10 to 40°C, preferably 20 to 35°C.
[0086] As the drying method in each of the above-mentioned production methods, various drying methods can be used, and either stationary drying or fluidized drying may be used. These methods may also be used in combination.
[0087] As described above, in this embodiment, the above different methods can be combined. Among them, the melt mixing method is preferred, and method (ii) is particularly preferred, in terms of productivity and the fact that a resin composition with more remarkable effects of the present invention can be obtained. In addition, when using the other thermoplastic resins and other compounding agents, they may be compounded by a conventional method according to the above manufacturing method.
[0088] The composition of the present invention obtained by each of the above-mentioned production methods may have any shape, but is preferably in the form of pellets. The pellets may be, for example, spherical, oval, cylindrical, die-shaped, rectangular, etc., but are usually oval or cylindrical. From the viewpoint of convenience when used later as a molding material, the size of the pellets is usually 1 to 10 mm, preferably 2 to 6 mm, more preferably 2.5 to 5.5 mm for the short diameter in the case of an oval shape, and usually 1.5 to 30 mm, preferably 3 to 20 mm, more preferably 3.5 to 10 mm for the long diameter. In addition, in the case of a cylinder, the diameter of the bottom surface is usually 1 to 6 mm, preferably 2 to 5 mm, and the length is usually 1 to 6 mm, preferably 2 to 5 mm. In addition, in the case of a die-shaped shape, one side is usually 1 to 6 mm, preferably 2 to 5 mm. Moreover, it is preferable that the shape and size of the pelletized EVOH resin used in each of the above-mentioned production methods are the same.
[0089] The water content of the present composition is not particularly limited, but is usually 0.01 to 0.5 mass %, preferably 0.05 to 0.35 mass %, and particularly preferably 0.1 to 0.3 mass %.
[0090] The water content of the composition is measured and calculated by the following method. The mass (W1) of this composition before drying is weighed on an electronic balance, dried in a hot air dryer at 150°C for 5 hours, and then cooled in a desiccator for 30 minutes, after which the mass (W2) is weighed and calculated using the following formula. [formula] Moisture content (mass%)=[(W1-W2) / W1]×100
[0091] In addition, when the composition is in the form of pellets, it is also preferable to attach a known lubricant to the surface of the pellets in order to stabilize the feedability during melt molding. Examples of the lubricant include higher fatty acids having 12 or more carbon atoms (e.g., lauric acid, myristic acid, palmitic acid, stearic acid, behenic acid, oleic acid, etc.), higher fatty acid esters (methyl esters, isopropyl esters, butyl esters, octyl esters, etc. of higher fatty acids), higher fatty acid amides (e.g., saturated higher fatty acid amides such as lauric acid amide, myristic acid amide, palmitic acid amide, stearic acid amide, behenic acid amide, etc.; unsaturated higher fatty acid amides such as oleic acid amide, erucic acid amide, etc.; bis-higher fatty acid amides such as ethylene bis-stearic acid amide, ethylene bis-oleic acid amide, ethylene bis-erucic acid amide, ethylene bis-lauric acid amide, etc.), low molecular weight polyolefins (e.g., low molecular weight polyethylenes having a molecular weight of about 500 to 10,000, low molecular weight polypropylenes, etc., or acid-modified products thereof), higher alcohols having 6 or more carbon atoms, ester oligomers, fluorinated ethylene resins, etc. These compounds can be used alone or in combination of two or more. The content of the lubricant is usually 5% by mass or less, preferably 1% by mass or less, of the composition. The lower limit is usually 0% by mass, for example, 0 to 5% by mass.
[0092] The composition thus obtained has excellent thermal stability, and the composition is visually analyzed using the IRIS VA400 (Alpha The ratio ("1363" + "1364" + "1365") / ("1636" + "1637" + "1638") of the sum of color numbers "1363" (R:88, G:88, B:56), "1364" (R:88, G:88, B:72), and "1365" (R:88, G:88, B:88) to the sum of color numbers "1636" (R:104, G:104, B:72), "1637" (R:104, G:104, B:88), and "1638" (R:104, G:104, B:104), measured using a chromatograph manufactured by MOS, is usually 1.8 or less, preferably 1.4 or less, and more preferably 1 or less. The lower limit is usually 0, for example, usually 0 to 1.8. The smaller the ratio, the more the coloring due to thermal degradation is suppressed, and the higher the thermal stability tends to be. Incidentally, a difference of 0.05 in the ratio is very significant since it appears as a large difference in yield in actual production.
[0093] <Molding material> The composition thus obtained is prepared into various forms, such as pellets, powder, or liquid, and is provided as a molding material for various molded products. In particular, in the present embodiment, when the composition is provided as a material for melt molding, the effects of the present invention tend to be more efficiently obtained, which is preferable.
[0094] Examples of the molded article include a monolayer film molded from the present composition, as well as a multilayer structure having a layer made of the present composition.
[0095] <Multilayer structure> A multilayer structure according to one embodiment of the present invention (hereinafter referred to as "the multilayer structure") contains the present composition and has at least one layer made of the present composition. The layer made of the present composition in the multilayer structure (hereinafter simply referred to as "the composition layer") may be a single layer or multiple layers. In addition, the present composition layer can be laminated with another substrate (hereinafter, the resin used in the substrate may be abbreviated as "substrate resin") mainly composed of a thermoplastic resin other than EVOH resin, to further impart strength, protect the present composition layer from the effects of moisture, etc., or impart other functions.
[0096] Examples of the base resin include polyethylene-based resins such as linear low-density polyethylene, low-density polyethylene, very low-density polyethylene, medium-density polyethylene, high-density polyethylene, ethylene-propylene (block and random) copolymers, and ethylene-α-olefin (α-olefin having 4 to 20 carbon atoms) copolymers; polypropylene-based resins such as polypropylene and propylene-α-olefin (α-olefin having 4 to 20 carbon atoms) copolymers; (unmodified) polyolefin-based resins such as polybutene, polypentene, and polycyclic olefin-based resins (polymers having a cyclic olefin structure in at least one of the main chain and side chain); and polyolefins obtained by treating with unsaturated carboxylic acids or Examples of the polyolefin resin include a broad definition of modified olefin resin, such as unsaturated carboxylic acid modified polyolefin resin graft-modified with the ester, ionomer, ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer, ethylene-acrylic acid ester copolymer, polyester resin, polyamide resin (including copolymerized polyamide), polyvinyl chloride, polyvinylidene chloride, acrylic resin, polystyrene resin, vinyl ester resin, polyester elastomer, polyurethane elastomer, polystyrene elastomer, halogenated polyolefin such as chlorinated polyethylene and chlorinated polypropylene, aromatic or aliphatic polyketones, etc. These may be used alone or in combination of two or more.
[0097] Of these, hydrophobic resins such as polyamide-based resins, polyolefin-based resins, polyester-based resins, and polystyrene-based resins are preferred, and more preferred are polyolefin-based resins such as polyethylene-based resins, polypropylene-based resins, polycyclic olefin-based resins, and unsaturated carboxylic acid-modified polyolefin-based resins thereof.
[0098] The layer structure of the multilayer structure may be any combination of a / b, b / a / b, a / b / a, a1 / a2 / b, a / b1 / b2, b2 / b1 / a / b1 / b2, b2 / b1 / a / b1 / a / b1 / b2, etc., where a is the composition layer and b is the base resin layer. In addition, when R is a recycled layer containing a mixture of the composition and a thermoplastic resin other than EVOH resin obtained by remelting and molding the ends and defective products generated in the process of manufacturing the multilayer structure, b / R / a, b / R / a / b, b / R / a / R / b, b / a / R / a / b, b / R / a / R / a / R / b, etc. The number of layers of the multilayer structure is usually 2 to 15, preferably 3 to 10 in total. In the above layer structure, an adhesive resin layer containing an adhesive resin may be interposed between the respective layers, if necessary.
[0099] The adhesive resin may be a known one, and may be appropriately selected according to the type of thermoplastic resin used in the base resin layer "b". A representative example is a modified polyolefin polymer containing a carboxy group obtained by chemically bonding an unsaturated carboxylic acid or its anhydride to a polyolefin resin by addition reaction, graft reaction, or the like. Examples of the modified polyolefin polymer containing a carboxy group include maleic anhydride grafted polyethylene, maleic anhydride grafted polypropylene, maleic anhydride grafted ethylene-propylene (block and random) copolymer, maleic anhydride grafted ethylene-ethyl acrylate copolymer, maleic anhydride grafted ethylene-vinyl acetate copolymer, maleic anhydride modified polycyclic olefin resin, maleic anhydride grafted polyolefin resin, etc. These may be used alone or in combination of two or more.
[0100] In the present multilayer structure, when an adhesive resin layer is used between the present composition layer and the base resin layer, since the adhesive resin layers are located on both sides of the present composition layer, it is preferable to use an adhesive resin with excellent hydrophobicity.
[0101] The above-mentioned base resin and adhesive resin may contain conventionally known plasticizers, fillers, clays (montmorillonite, etc.), colorants, antioxidants, antistatic agents, lubricants, nucleating agents, antiblocking agents, waxes, etc., within a range that does not impair the gist of the present invention (for example, usually 30% by mass or less, preferably 10% by mass or less, with the lower limit being 0% by mass, for example 0 to 30% by mass, based on the total resin). These may be used alone or in combination of two or more kinds.
[0102] The lamination of the composition layer and the above-mentioned substrate resin layer (including the case where an adhesive resin layer is interposed) can be performed by a known method. For example, a method of melt extrusion laminating a substrate resin to a film, sheet, etc. of the composition, a method of melt extrusion laminating the composition to a substrate resin layer, a method of co-extruding the composition and the substrate resin, a method of dry laminating the composition (layer) and the substrate resin (layer) using a known adhesive such as an organic titanium compound, an isocyanate compound, a polyester compound, a polyurethane compound, etc., a method of applying a solution of the composition on a substrate resin and then removing the solvent, etc. Among these, in consideration of cost and environmental aspects, it is preferable to manufacture by providing a step of melt molding a layer including the composition layer, and specifically, a co-extrusion method is preferable.
[0103] The multilayer structure may be subjected to a (heat) stretching treatment as necessary. The stretching treatment may be either uniaxial stretching or biaxial stretching, and in the case of biaxial stretching, it may be simultaneous stretching or sequential stretching. As the stretching method, a method with a high stretch ratio among roll stretching, tenter stretching, tubular stretching, stretch blowing, vacuum pressure molding, etc. may be adopted. The stretching temperature is a temperature near the melting point of the multilayer structure, and is usually selected from the range of 40 to 170°C, preferably about 60 to 160°C. When the stretching temperature is equal to or higher than the lower limit, the stretchability tends to be excellent, and when the stretching temperature is equal to or lower than the upper limit, a stable stretched state tends to be easily maintained.
[0104] The multilayer structure after the stretching treatment may be heat-set for the purpose of imparting dimensional stability. Heat setting can be performed by a known means, for example, the multilayer structure after the stretching treatment is heat-treated usually at 80 to 180°C, preferably 100 to 165°C, for usually about 2 to 600 seconds while being kept in a tensioned state.
[0105] When the stretched multilayer structure is to be used as a shrink film, the above-mentioned heat fixing may be omitted in order to impart heat shrinkability, and instead, a treatment such as cooling and fixing the multilayer structure after the stretching treatment by applying cold air thereto may be carried out.
[0106] The thickness of the present multilayer structure (including the stretched one), and further the thickness of the present composition layer, the base resin layer and the adhesive resin layer constituting the multilayer structure, cannot be generally stated depending on the layer structure, the type of base resin, the type of adhesive resin, the purpose, the packaging form, the required physical properties, etc., but the thickness of the present multilayer structure (including the stretched one) is usually 10 to 5000 μm, preferably 30 to 3000 μm, and particularly preferably 50 to 2000 μm. The present composition layer is usually 1 to 500 μm, preferably 3 to 300 μm, and particularly preferably 5 to 200 μm, the base resin layer is usually 5 to 3000 μm, preferably 10 to 2000 μm, and particularly preferably 20 to 1000 μm, and the adhesive resin layer is usually 0.5 to 250 μm, preferably 1 to 150 μm, and particularly preferably 3 to 100 μm.
[0107] Furthermore, the thickness ratio of the present composition layer to the base resin layer in the present multilayer structure (present composition layer / base resin layer) is usually 1 / 99 to 50 / 50, preferably 5 / 95 to 45 / 55, and particularly preferably 10 / 90 to 40 / 60, when there are multiple layers of each, and the thickness ratio of the present composition layer to the adhesive resin layer in the present multilayer structure (present composition layer / adhesive resin layer) is usually 10 / 90 to 99 / 1, preferably 20 / 80 to 95 / 5, and particularly preferably 50 / 50 to 90 / 10, when there are multiple layers of each ....
[0108] <Molded body> It is also possible to obtain a cup- or tray-shaped molded body using this multilayer structure. In that case, a squeeze molding method is usually used, specifically, a vacuum molding method, a pressure molding method, a vacuum pressure molding method, a plug-assisted vacuum pressure molding method, etc. are exemplified. Furthermore, when a tube- or bottle-shaped multilayer container (laminate structure) is obtained from a multilayer parison (a hollow tubular preform before blowing), a blow molding method is employed. Specifically, an extrusion blow molding method (double-head type, mold moving type, parison shift type, rotary type, accumulator type, horizontal parison type, etc.), a cold parison type blow molding method, an injection blow molding method, a biaxial stretch blow molding method (extrusion type cold parison biaxial stretch blow molding method, injection type cold parison biaxial stretch blow molding method, injection molding in-line type biaxial stretch blow molding method, etc.) are exemplified. The resulting laminate may be subjected to processes such as heat treatment, cooling, rolling, printing, dry lamination, solution or melt coating, bag making, deep drawing, box processing, tube processing, and splitting, as required.
[0109] <Package> Packaging products such as single layer films formed from the present composition, and containers and lids formed from bags, cups, trays, tubes, bottles, etc. made of the present multilayer structure are useful as various packaging material containers (e.g., food packaging, drug packaging, cosmetic packaging) for general foods as well as seasonings such as mayonnaise and dressings, fermented foods such as miso, oily foods such as salad oil, beverages, cosmetics, pharmaceuticals, etc. EXAMPLES
[0110] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples as long as it does not depart from the gist of the invention. In the examples, "parts" and "%" are based on mass.
[0111] Prior to the examples, the following EVOH resins were produced and prepared. (Production of ethylene-vinyl acetate copolymer) A polymerization vessel was charged with 100 parts of vinyl acetate, the carbon of which was derived from biomass, and 16 parts of methanol. The system was replaced with nitriding gas once, and then replaced with ethylene, and ethylene was pressurized until the pressure reached 4.12 MPa. Under ethylene pressure, the temperature was raised to 67°C while stirring, and peroxyester was added at a rate of 0.05 parts / hr for 4 hours while reacting for a total of 6 hours to obtain an ethylene-vinyl acetate copolymer. The polymerization rate of the obtained ethylene-vinyl acetate copolymer was 56%.
[0112] (Production of EVOH resin) To 100 parts of a methanol solution containing 50% of the above ethylene-vinyl acetate copolymer, 70 parts of a methanol solution containing 0.02 equivalents of sodium hydroxide relative to the remaining vinyl acetate groups in the copolymer were added, and a saponification reaction was carried out at 80°C for 80 minutes. Next, 100 parts of a methanol aqueous solution having a water content of 50% was supplied to the methanol solution of the EVOH resin under azeotropic conditions, and methanol was distilled off until the resin concentration in the methanol / aqueous solution of the EVOH resin reached 40%, thereby obtaining a completely transparent methanol / water homogeneous solution of the EVOH resin. Next, the obtained methanol / water solution of the EVOH resin was solidified into a thin plate, which was then cut with a knife to obtain a die-shaped pellet having a side length of 3 mm. The resulting die-shaped pellets were washed for 30 minutes with 250 parts of treated water containing 5 parts of acetic acid per 100 parts of pellets. The treated water was replaced and washed three times. Next, the resulting die-shaped pellets were washed for 30 minutes with 250 parts of water per 100 parts of pellets. The water was replaced and washed twice. Next, the resulting die-shaped pellets were dried at 118°C for 8 hours under a nitrogen gas flow with an oxygen concentration of 0.5% by volume or less to obtain pellets of EVOH resin (ethylene structural unit content 32 mol%, saponification degree 99.7 mol%, bio-based degree 64% (bio-vinyl alcohol structural unit content of the total vinyl alcohol structural units is 94%).
[0113] <Example 1> (Production of titanium compound and lubricant-containing composition pellets) The obtained EVOH resin pellets, rutile-type titanium oxide (IV) with an average particle size of 5 μm or less (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) as a titanium compound, and lubricant "Alflo H50-FP" (manufactured by NOF Corporation) were used. The EVOH resin pellets were melt-kneaded in a benchtop kneader "Xplore-HTMC15HT (15 mL capacity)" (manufactured by LeoLabo) under the following kneading conditions so that the titanium oxide content in terms of metal was 0.04 ppm and the lubricant content was 8000 ppm relative to the mass of the composition, and the extruded and discharged strands were cooled and solidified by air cooling to obtain pellets of the composition. [Mixing conditions] Small mixer temperature: 200℃ Screw shape: Twin conical type Screw rotation: same direction Mixing time: 10 minutes
[0114] <Example 2> A composition was obtained in the same manner as in Example 1, except that the content of the lubricant in Example 1 was changed to 40 ppm based on the mass of the composition.
[0115] <Example 3> A composition was obtained in the same manner as in Example 1, except that the content of titanium oxide in terms of metal was changed to 0.1 ppm relative to the mass of the composition, and the content of the lubricant was changed to 200 ppm relative to the mass of the composition.
[0116] <Comparative Example 1> A composition was obtained in the same manner as in Example 1, except that the content of the lubricant in Example 1 was changed to 4 ppm based on the mass of the composition.
[0117] <Comparative Example 2> A composition was obtained in the same manner as in Example 1, except that the content of the lubricant in Example 1 was changed to 12,000 ppm based on the mass of the composition.
[0118] <Comparative Example 3> A composition was obtained in the same manner as in Example 3, except that the content of the lubricant in Example 3 was changed to 40 ppm based on the mass of the composition.
[0119] <Comparative Example 4> A composition was obtained in the same manner as in Example 1, except that the content of titanium oxide in terms of metal was changed to 3 ppm relative to the mass of the composition, and the content of the lubricant was changed to 0 ppm relative to the mass of the composition.
[0120] The following thermal stability evaluation was carried out using the obtained compositions of Examples 1 to 3 and Comparative Examples 1 to 4. The results are shown in Table 1 below.
[0121] [Evaluation of Thermal Stability] The obtained composition was cut with a nipper and pulverized to prepare a sample. Using a visual analyzer IRIS VA400 (manufactured by Alpha mos), the ratio of the sum of color numbers "1363" (R: 88, G: 88, B: 56), color numbers "1364" (R: 88, G: 88, B: 72), and color numbers "1365" (R: 88, G: 88, B: 88) to the sum of color numbers "1636" (R: 104, G: 104, B: 72), color numbers "1637" (R: 104, G: 104, B: 88), and color numbers "1638" (R: 104, G: 104, B: 104) ("1363" + "1364" + "1365") / ("1636" + "1637" + "1638") was evaluated. The color numbers "1636", "1637", and "1638" are colors with a light yellow tint, while the color numbers "1363", "1364", and "1365" are colors with a deep yellow tint. The smaller this ratio is, the more the yellow coloring is suppressed and the higher the thermal stability is.
[0122] [Table 1]
[0123] As can be seen from the results in Table 1 above, the compositions of Examples 1 to 3, which contain a specific trace amount of a titanium compound and a specific mass ratio of the lubricant and the titanium compound, have a lower proportion of deep yellowness (for example, Example 1 is 20% or more lower than Comparative Example 1, and 60% or more lower than Comparative Example 2) and have excellent thermal stability compared to the compositions of Comparative Examples 1 to 4, which do not contain a specific trace amount of a titanium compound and a specific mass ratio of the lubricant and the titanium compound. Furthermore, the multilayer structures having layers made of the compositions of Examples 1 to 3 also have excellent thermal stability, and molded articles and food packages containing such multilayer structures also have excellent thermal stability. [Industrial Applicability]
[0124] Because the present composition has excellent thermal stability, it is useful as a packaging material for various foods, as well as seasonings such as mayonnaise and dressings, fermented foods such as miso, oily foods such as salad oil, beverages, cosmetics, pharmaceuticals, etc.
Claims
1. A composition comprising an ethylene-vinyl alcohol copolymer, a titanium compound, and a lubricant, At least a portion of the ethylene-vinyl alcohol copolymer is derived from biomass; The content of the titanium compound in terms of metal is 0.0001 ppm or more and less than 1 ppm based on the mass of the composition, A composition, wherein a mass ratio of the content of the lubricant to the content of the titanium compound calculated as metal is 500 to 280,000.
2. 2. The composition according to claim 1, wherein the content of the titanium compound in terms of metal is 0.0001 ppm or more and 0.8 ppm or less based on the mass of the composition.
3. 2. The composition of claim 1, wherein the ethylene-vinyl alcohol copolymer has a bio-based content of 0.01 to 99%.
4. 2. The composition of claim 1, wherein the ethylene-vinyl alcohol copolymer has a biobased content of 1 to 99%.
5. A molding material comprising the composition according to any one of claims 1 to 4.
6. A multi-layer structure having a layer comprising the composition according to any one of claims 1 to 4.
7. The multilayer structure of claim 6 further comprising an adhesive resin layer.
8. A molded article comprising the multilayer structure according to claim 6.
9. A food package comprising the multi-layer structure of claim 6.
10. A method for producing a composition according to any one of claims 1 to 4, comprising the steps of: A method for producing a composition comprising the step of mixing the ethylene-vinyl alcohol copolymer and the titanium compound.
11. A method for producing the multi-layer structure of claim 6, comprising the steps of: A method for producing a multilayer structure, comprising the step of melt-molding a layer comprising the composition.
Citation Information
Patent Citations
Gas barrier resin composition, multilayer structure, and method for producing gas barrier resin composition
JP2022013857A
Gas-barrier resin composition, multilayer sheet, packing material, and container
JP2022027726A